2019
DOI: 10.1016/j.ijppaw.2019.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Air sac trematodes: Morishitium polonicum as a newly identified cause of death in the common blackbird (Turdus merula)

Abstract: Necropsy of two free-ranging common blackbirds ( Turdus merula ) found dead in central Italy revealed the presence of a high number of cyclocoelid flukes in the coelomatic cavity. Cyclocoelid flukes primarily infect avian respiratory system. Histologically, air sac walls were covered with a fibrinous exudate containing degenerate heterophils, many trematodes and some colonies of Gram-positive cocci. The superficial bronchi and parabronchi were markedly distended, and the adjacent pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Although mild associated lesions were showed in most infected animals in this study, only one bird revealed a massive infection (72 adult trematodes in the coelomic cavity) with severe damage in several organs (tracheitis, aerosaculitis, enteritis and hepatitis). This trematode has been previously described on Turdidae from different European countries such as Spain [1], Poland [14] or Italy [4]. Birds get infected through the consumption of wetland-associated mollusks.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…Although mild associated lesions were showed in most infected animals in this study, only one bird revealed a massive infection (72 adult trematodes in the coelomic cavity) with severe damage in several organs (tracheitis, aerosaculitis, enteritis and hepatitis). This trematode has been previously described on Turdidae from different European countries such as Spain [1], Poland [14] or Italy [4]. Birds get infected through the consumption of wetland-associated mollusks.…”
Section: Resultsmentioning
confidence: 82%
“…Birds get infected through the consumption of wetland-associated mollusks. Although there is scarce information about the pathology related to M. polonicum infection, airsacculitis, bronchitis and peribronchitis have been recently described in Turdus merula [4]. However, this is the first report of severe enteric and hepatic lesions associated to M. polonicum infection in Turdidae.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The typical host of the parasite is Turdus philomelos Brehm, 1831. Morishitium polonicum was previously registered in thrushes in Poland (Machalska, 1980;Sulgostowska & Czaplinska, 1987), Italy (Visconti et al, 1988;Bona et al, 1995;Galosi et al, 2019), the Czech Republic (Sitko et al, 2017), and Spain (Jaume-Ramis & Pinya, 2018). The parasite was also noted in Armenia, Azerbaijan, Georgia, and Uzbekistan as Neocyclocoelum elongatum (Harrah, 1921) (Feizullaev, 1980).…”
Section: Description Of Trematodes From Coccothraustes Coccothraustesmentioning
confidence: 94%